ANALYSIS OF CONCEPTUAL UNDERSTANDING OF FASHION DESIGN EDUCATION STUDENTS IN THE LEARNING OUTCOME EVALUATION COURSE - Purnamasari, Untung Desy (Universitas Negeri Medan, 2025)
Abstract This study aims to describe the conceptual understanding of fashion design education students in the learning outcome evaluation course. The sample of this research were 30 fashion design education students from the 2023 intake. The method used in this research was descriptive. Data collection was carried out using test techniques in essay form. The results of the research showed that the average test related to the conceptual understanding of fashion design education students in the learning outcome evaluation course was 13.57, which is included in the moderate category. The results of the analysis per indicator of conceptual understanding were that students were lacking in repeating concepts, classifying types of objects based on certain characteristics according to the concept, determining examples and non-examples of the concept, and obtaining information on sufficient and necessary conditions for a concept. Keywords: conceptual understanding, learning outcome evaluation course